Therapeutic Management of Renal Dysfunction Associated with Trypanosomiasis in a Horse - A Case Report - Vidhyalakshmi, TM; Raval, SK; Akshatha, GM; Parikh, PV; Kathri, JM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Trypanosomiasis, an arthropod borne blood protozoan disease commonly known as Surra is caused by Trypanosoma evansi. Several species of hematophagous flies, including Tabanids and Stomoxys are implicated in transferring infection from host to host, acting as mechanical vectors. Trypanosomiasis is diagnosed based on the clinical evidences augmented with some parasitological methods. The “Office international des epizootics” categorized the disease under ‘B’ disease of significance (OIE, 2004). Surra in India is generally considered as a disease prevalent mostly in animals of Northern India (Soodan et al., 1995). The present case deals with the diagnosis of renal dysfunction associated with trypanosomiasis and its’ successful therapeutic management in a mare. Case History and Clinical Observations A seven year old mare with a history of reduced feed intake was presented to Teaching Veterinary Clinical Complex, Anand. Clinical manifestations included fever, depression and edema on brisket and ventral region of the body. Clinical examination revealed pyrexia (103.3°F), tachycardia (60 beats/min) and pale to icteric mucous membrane. There was a history of prophylactic therapy against trypanosomes two months back.